Towards developing an indoor emissions inventory for the UK: challenges and future directions - Mazzeo, Andrea; Pfrang, Christian; Nasir, Zaheer A. (Royal Society of Chemistry (RSC), 2025)
The global attention on indoor air quality is progressively increasing as people spend ca. 80 to 90% of their lives indoors. Therefore, a substantial fraction of exposure to air pollution occurs in different indoor environments. However, there is a lack of information on how different time and activity dependent sources and built environment characteristics affect air pollutant emissions and their distribution. There is an urgent need to develop indoor emissions inventories to estimate the contribution of multiple and time-dependent sources and activities to air pollutant emissions. This paper reviews the current state-of-the-art of indoor air pollution research in the UK, categorises the published literature according to pollutant types, built environments and activities, provides an overview of typical levels of indoor air pollutants with a focus on UK-specific measurements and identifies the research gaps and future directions to progress towards developing indoor emission inventories. In the UK, researchers have investigated indoor air quality since the nineties producing many studies from different perspectives. However, a cohesive methodological approach is lacking in most of the studies. Several important sources/species are not represented, ancillary information relating to environment characteristics (volumes and ventilation) and occupants' behaviours during the measurements is not reported and too little information on the indoor–outdoor continuum is provided. Despite the gaps identified, the existing evidence base on indoor air pollution in the UK can be categorised in an easy-to-use database of indoor air pollutant concentrations and characteristic emission rates for specific activities, pollutants and environments. This will provide a platform for designing standardised approaches for indoor air quality measurements and the development of activity-based indoor emission inventories, which will be a step-change in indoor air pollution research in the UK and globally.
Keywords: 41 Environmental Sciences; 4105 Pollution and Contamination; Climate-Related Exposures and Conditions; Social Determinants of Health; 2.2 Factors relating to the physical environment; 3.2 Interventions to alter physical and biological environmental risks; Respiratory; Generic health relevance